Progress in Clinical Diagnosis and Management of Short Stature in Ehlers-Danlos Syndromes - XU Kexin; LI Guozhuang; WU Zhihong; ZHANG Jianguo; DISCO(Deciphering Disorders Involving Scoliosis & Comorbidities) Study Group; WU Nan (Xiehe Yixue Zazhi)
Ehlers-Danlos syndromes (EDS) are a group of rare hereditary connective tissue disorders characterized by joint hypermobility, skin hyperextensibility, and tissue fragility. Short stature is defined as a height that is two standard deviations or more below the average height for individuals of the same age, sex, and race. The etiopathogenesis of short stature is complicated. Early detection and appropriate intervention are essential in disease treatment. However, short stature is not common among all EDS subtypes. It is frequently observed in patients with rare subtypes, such as spondylodysplastic EDS, dermatosparaxis EDS, and musculo-contractural EDS. Besides, height may be affected by other factors including spinal curvature and malnutrition. Deep phenotyping and multidisciplinary team approaches are recommended for the diagnosis and management. Short stature in patients with EDS has not been sufficiently acknowledged in China. There is currently a lack of high-level evidence for the treatment of EDS-related short stature. Therefore, this review aims to present recent progress of diagnosis and management of short stature in patients with EDS. Further studies focusing on short stature in rare subtypes are necessary to advance precision medicine and enhance patient care.